Glutamatergic synaptic resilience to overexpressed human alpha-synuclein - Patrícia I. Santos; Inés Hojas García-Plaza; Ali Shaib; Jeong Seop Rhee; Abed Alrahman Chouaib; Nils Brose; Silvio O. Rizzoli; James Daniel; Tiago F. Outeiro (npj Parkinson's Disease)
Abstract Alpha synuclein (aSyn) is abundant in the brain and strongly implicated in Parkinson’s disease (PD), genetically and through its accumulation in neuronal pathognomonic inclusions. While mutations or increased expression of wild-type aSyn can cause familial PD, it remains unclear whether increased aSyn alone impairs presynaptic function. Here, we overexpressed human aSyn (haSyn) in rodent glutamatergic neurons and analysed presynaptic function. Expression levels mimicked SNCA gene triplications, as seen in certain familial forms of PD. In continental cultures, haSyn overexpression was not toxic nor did it alter the levels of presynaptic SNAP-25 or postsynaptic PSD-95. Analyses of autaptic neurons revealed no significant differences in evoked or spontaneous neurotransmission release, nor in synaptic plasticity. These results indicate that rodent glutamatergic neurons are resilient to aSyn overexpression. Our findings suggest neurotoxicity associated with aSyn overexpression is not universal, and that a deeper understanding of aSyn biology and pathobiology is necessary.